Evaluation of treatment for diffuse large B-cell lymphoma using plasma D-dimer levels - Ruonan Shao; Danchen Meng; Beibei Gao; Lu Zhang; Qingqi Meng; Yanqiu Hou; Zhangbiao Long; Jinsong Yan; Xiaofeng Shi (Scientific Reports)
Abstract It has been documented that D-dimer levels have potential utility as a measure of tumor activity in diffuse large B-cell lymphoma (DLBCL), however whether it can be used as a predictive marker of treatment outcome has not been established. This study means to retrospectively evaluate the role of D-dimer in prediction of treatment efficacy in patients with DLBCL. 151 patients with newly diagnosed DLBCL were enrolled. Blood samples were taken from those patients during the initial visit to our hospital and again after two cycles of chemotherapy to measure D-dimer levels. The link between plasma D-dimer concentrations and patients’ clinical characteristics was explored before and after treatment. D-dimer levels within the range of 0–1 µg/mL were considered negative, while readings above this range were considered positive. D-dimer difference percentage (Ddp) represents the percentage change in D-dimer levels before and after chemotherapy, calculated as (post-chemotherapy D-dimer minus pre-chemotherapy D-dimer) / pre-chemotherapy D-dimer × 100. Patients showed statistically different plasma D-dimer levels at initial consultation across treatment-response groups: CR (0.63 µg/mL [0.43–1.27]), PR (1.39 µg/mL [0.73–2.46]), SD (0.89 µg/mL [0.59–1.24]), and PD (1.34 µg/mL [0.67–2.62]). After chemotherapy, the PR group exhibited a mean D-dimer level of -0.38 µg/mL (range − 1.64 to -0.11), which was significantly lower than that of the PD group (mean 0.04 µg/mL, range − 0.40 to 0.79; p < 0.05). The CR group revealed significantly lower initial D-dimer levels (median 0.63 µg/mL) and greater reductions after chemotherapy compared to the non-CR group (median 1.17 µg/mL, p < 0.05). Patients with coagulation disorders such as DIC, DVT, or PE were excluded to minimize confounding factors. While this study demonstrates the utility of D-dimer in predicting short-term treatment response, the relationship with long-term outcomes such as PFS and OS requires further investigation. Patients who respond well to chemotherapy typically exhibit lower D-dimer levels at the initial diagnosis. Those in the SD or PD groups usually experience a greater increase in D-dimer levels following chemotherapy. Consequently, variations in plasma D-dimer levels before and after treatment may offer valuable insights for evaluating the efficacy of chemotherapy treatment.